PERAN ORANGTUA DALAM MENINGKATKAN MOTIVASI BELAJAR ANAK USIA 10-14 TAHUN DI DESA SIBORBORON KEC.SIJAMAPOLANG KAB. HUMBANG HASUNDUTAN - Ayu Lestari R.Simanullang; Drs. Elizon Nainggolan, M.Pd (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the role of parents in enhancing children's learning motivation. The research was conducted in Siborboron Village, Sijamapolang District, Humbang Hasundutan Regency. This study uses a qualitative descriptive method. The research subjects were four parents and four children from Siborboron Village. Data collection techniques used were observation, interviews, and documentation. The data analysis process included data collection, data reduction, data presentation, and drawing conclusions. Data validity was ensured through source triangulation and technique triangulation. The results show that parents play roles as role models, facilitators, and motivators in improving children's learning motivation. The motivational strategies provided by parents include giving praise, rewards, and sanctions. Based on the analysis, it can be concluded that the role of parents in enhancing children's learning motivation is not yet optimal because the children still receive insufficient attention in learning at home due to parents being busy working in the fields.